Enhanced reliability by diamond-like carbon in single-layer organic light emitting diodes - Yap, S.-S.; Yang, R.-B.; Yow, H.-K.; Tou, T.-Y. (2006)
Diamond-like carbon (DLC) layers with thickness of 1.5 nm were incorporated, by pulsed laser deposition technique, in organic light emitting diodes (OLEDs), which consisted of a single light-emitting layer of polystyrene (PS) as the host material, but co-doped with N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD) and Tris-(8-hydroxyquinoline)-Aluminium (Alq(3)). For unstable ITO/doped-PS/Al OLEDs, which easily failed with poor light emission when the doped-PS layer used was too thin, the insertion of DLC in the ITO/doped-PS/DLC/Al structure restored the device operation to maximum operating voltage and hence full brightness.